Unveiling Depths The Regional Language Research in Brunei: Preservation, Globalization, and Cultural Identity using Bibliometric Analysis (International Journal of Linguistics and Indigenous Culture, 2024)
By unravelling these complicated threads, the study provides insight into the interconnections among concepts, seminal contributions, and thematic evolution within this field. Research on the impact of globalization on local dialects is experiencing a simultaneous surge. The main focus of important academic works highlights the urgent necessity to safeguard languages and the intricate dynamics of the global dominance of Brunei's linguistic heritage. This scholarly investigation offers a thorough examination of the intricate progress in regional language research within Brunei, focusing on the relationship between preservation, globalisation, and cultural identity. This study uses bibliometric analysis and VOSviewer visualisation to investigate the scholarly landscape of Brunei's linguistic domain thoroughly. Publication patterns have evolved over time, starting from basic documentation of linguistic differences to now involving interdisciplinary partnerships that bridge linguistics with sociology and education. This study employs bibliometric analysis to examine the complex relationships and patterns that influence regional language research in Brunei. After refining the keywords, the study found only 43 documents out of 996 to be relevant. It was observed that articles were the most commonly published type, with Springer and Universiti Brunei Darussalam being the top publishers for studies on regional languages in Brunei. In VOSviewer analysis, the themes of 'tradition' and 'heritage' emerged as dominant, highlighting the importance of language and culture research in preserving linguistic heritage for future generations. Keyword: bibliometric analysis, VOSview, regional language, evolution, Brunei